Problem Based Learning: Gender Responsive Alternative Learning Models for Vocational High Schools - Komariah, Kokom; Sofyan, Herminarto; Wagiran; Mahfud, Tuatul (International Journal of Psychosocial Rehabilitation, 2020)
Many studies have addressed gender disparities in various fields, but specializing in solutions through learning activities has not been done much. This study aims to explore problem-based learning as alternative learning that is responsive to gender in Vocational High Schools. Data were collected with a technical survey and involved vocational teachers. Data analysis uses descriptive statistics. The results of the study revealed that the teacher did not understand well the concept of gender in learning. Male students dominate the utilization of learning facilities. Also, problem-based learning can be implemented through 6 stages, namely the introduction, organizing, investigating, developing the results of the investigation and presenting the work, analysis, and evaluation of the problem-solving process. Problem-based learning can encourage fair learning. Finally, the problem-based learning model can increase the active participation of students through interactive activities in apperception, asking questions, expressing opinions, answering questions, and completing assignments.